Mahmood Merican Award for Masters in Orthopaedic Surgery Trainees in Malaysia - Ahmad, T.S. (2011)
The Mahmood Merican Award is an annual award for the best original scientific or clinical study submitted by young trainees in orthopaedic surgery in Malaysia, for presentation during the annual scientific meeting of the Malaysian Orthopaedic Association (MOA). This award was initiated in 1997 to encourage high standard of research and scientific presentations among young trainees.A cash prize of RM 1,000 was donated by Dato Dr Mahmood Merican. All Award finalists will represent MOA as ambassadors to regional orthopaedic association meetings, a duty that will be fully sponsored by MOA.